Nastopanje skupnosti etažnih lastnikov v sodnih postopkih - Napotnik, Anita (Pravni letopis, 2014)
The establishment of floor ownership as a special right in rem has also caused the development of a special community named the community of floor owners which is based on this special right. This community, as a new legal entity in civil law, needs appropriate legal protection. The Slovenian legal order does not allocate to the community of floor owners either the legal capacity or the capacity to sue. There are no rules which would define the appearance of the community of floor owners in civil procedures. These legal lacunas are filled by court decisions which are not harmonized. In general in their decisions the courts are not keen on providing legal capacity for the community of floor owners to enter the procedures. Party to the proceeding, if it is allowed, is based on 76/3 of the Civil Procedure Act (grant capacity to be a party). It would be reasonable for the community of floor owner to be recognized their partial legal capacity and capacity to sue and to be sued. This would enable the community to be identified as a party in civil litigations.
Keywords: etažna lastnina; pooblastila; pristojnosti; sodni postopek; stanovanjske zgradbe